The moderating effect of gender and education level on safe food handling intention among consumers in Sibu, Malaysia: based on the Theory of Planned Behavior - Genevie Eleanor, Ruby; Ungku Fatimah, Ungku Zainal Abidin; Lihan, Samuel; Nuzul Noorahya, Jambari; New, C.Y.; Son, R. (Rynne Lyan Resources, 2020)
The consumers who did not comply with safe food-handling practices also contributed to the occurrence of food contamination. This study adapted the Theory of Planned Behavior (TPB) to examine the moderating effect of gender and level of education differences that influence the intention of safe food handling at home. A total of 623 consumers based in Sibu, Malaysia completed a questionnaire that measured attitude, subjective norm, perceived behavior control (PBC), and intention. Based on PLS-SEM multi-group analysis (PLS-MGA) by permutation approach, gender demonstrated no moderating effect on the TPB relationships in each state. Meanwhile, the level of education was a significant moderator between PBC and intention. In this relationship, it was indicated that PBC for consumers from lower education group was stronger than their counterparts. These results offered useful information for local authorities or educational institutions to gain a better understanding of consumer behavior towards safe food handling, allowing the authorities to develop intervention accordingly.